The Current Situation of Financial Aid Policies and Social Support for Impoverished College Students in China: a Literature Review - Li, Xianfu; Lee, Seungjin (Journal of Educational Research and Policies, 2024)
This paper starts from the concept of impoverished college students and describes in detail the five stages of China's financial aid policies for impoverished college students. It elaborates on the basic situation of impoverished college students in China from three aspects: learning status, mental health status, and employment status. Finally, based on previous research, this study divides social support into national support, school support, third-party social force support, teacher support, family support, and peer support. This study provides insight into the situation of financial aid for impoverished students in Chinese universities and provides a reference for future policy formulation and research.